2008
DOI: 10.1111/j.1939-1676.2008.0100.x
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Chronic Eosinophilic Pneumonia in 7 Horses

Abstract: Background: Idiopathic chronic eosinophilic pneumonia of horses is incompletely described. Objectives: To describe the physical examination, clinicopathologic, histopathologic, and radiographic features and response to corticosteroid treatment of idiopathic chronic eosinophilic pneumonia of horses.Animals: Seven horses with eosinophilic pneumonia. Methods: Retrospective, descriptive study.Results: Anamnesis, clinical signs, and clinicopathologic and radiologic findings in 7 adult horses with histologically con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 24 publications
(25 reference statements)
1
29
1
Order By: Relevance
“…In both studies, vasculitis was not reported. 6,7 In the present case series based on histologic findings and the absence of an etiologic agent, a diagnosis of idiopathic eosinophilic pneumonia with associated vasculitis was made. Interestingly vasculitis has not been described in lungs of horse with eosinophilic pneumonia before this study.…”
Section: Bell Et Almentioning
confidence: 84%
See 1 more Smart Citation
“…In both studies, vasculitis was not reported. 6,7 In the present case series based on histologic findings and the absence of an etiologic agent, a diagnosis of idiopathic eosinophilic pneumonia with associated vasculitis was made. Interestingly vasculitis has not been described in lungs of horse with eosinophilic pneumonia before this study.…”
Section: Bell Et Almentioning
confidence: 84%
“…[3][4][5][6][7] Eosinophilic infiltrates of equine lungs are observed during parasitic infections or allergic condition 8,9 but eosinophilic pneumonia with vasculitis, which are not associated with parasitic infection and without the evidence of involvement of other organs have not been previously reported in horses. In the present study, we describe the gross and microscopic lesions of idiopathic eosinophilic pneumonia with associated vasculitis in 11 horses.…”
mentioning
confidence: 96%
“…Eosinophilic inflammation in BALF is typically more severe and persistent in parasitic pneumonitis and idiopathic eosinophilic pneumonia than in eosinophilic IAD 100, 102. Furthermore, direct examination of tracheal wash fluid might reveal the presence of larvae.…”
Section: Differential Diagnosesmentioning
confidence: 99%
“…[215][216][217][218] Included in this syndrome are inflammatory airway disease (IAD, mild to moderate equine asthma) and recurrent airway obstruction (RAO, severe equine asthma). [223][224][225][226] It is not uncommon for horses to cough occasionally, especially at the beginning of exercise. RAO primarily affects horses over 7 years of age.…”
Section: Causes Of Cough Without Fevermentioning
confidence: 99%
“…Acute viral infection can be associated with leukopenia characterized primarily by lymphopenia. 216,[224][225][226] Hypercalcemia can be seen in some horses with malignancy. Neutrophilia and hyperfibrinogenemia are seen with many inflammatory conditions, especially bacterial or fungal pneumonia.…”
Section: Ancillary Diagnostic Testsmentioning
confidence: 99%